BIOLOGIA DA TRAÃ‡A DOS FAVOS, ð˜Žð˜¢ð˜ð˜ð˜¦ð˜³ð˜ªð˜¢ ð˜®ð˜¦ð˜ð˜ð˜°ð˜¯ð˜¦ð˜ð˜ð˜¢ L., 1758 (Galleriidae, Lepidoptera) - Flechtmann, Carlos H. W. (REVISTA DE AGRICULTURA, 2020)
BIOLOGIA DA TRAÃ‡A DOS FAVOS, ð˜Žð˜¢ð˜ð˜ð˜¦ð˜³ð˜ªð˜¢ ð˜®ð˜¦ð˜ð˜ð˜°ð˜¯ð˜¦ð˜ð˜ð˜¢ L., 1758 (Galleriidae, Lepidoptera)